2014
DOI: 10.1007/s00023-014-0331-7
|View full text |Cite
|
Sign up to set email alerts
|

BTZ Black Hole Entropy and the Turaev–Viro Model

Abstract: We show the explicit agreement between the derivation of the Bekenstein-Hawking entropy of a Euclidean BTZ black hole from the point of view of spin foam models and canonical quantization. This is done by considering a graph observable (corresponding to the black hole horizon) in the Turaev-Viro state sum model, and then analytically continuing the resulting partition function to negative values of the cosmological constant.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 77 publications
(144 reference statements)
1
9
0
Order By: Relevance
“…It is also worth mentioning that in the calculation of [7] (formula (16)) the entropy was dominated by small spins, whereas according to loop quantum gravity [6], it is the large spins which dominate the entropy. In the present paper we have agreed with the loop quantum gravity calculation at least in that direction since after considering the Wick rotation we have freed ourselves from the spin dependence of formula (16).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…It is also worth mentioning that in the calculation of [7] (formula (16)) the entropy was dominated by small spins, whereas according to loop quantum gravity [6], it is the large spins which dominate the entropy. In the present paper we have agreed with the loop quantum gravity calculation at least in that direction since after considering the Wick rotation we have freed ourselves from the spin dependence of formula (16).…”
Section: Discussionsupporting
confidence: 81%
“…In [16] the method followed to compute the entropy of BTZ resembles ours and at the same time improves our result by proceeding with innovative ideas. The solid torus is triangulated with an even number of edges at the horizon.…”
Section: The Btz Black Hole Entropymentioning
confidence: 66%
See 2 more Smart Citations
“…It has been suggested that the corresponding partition function can be obtained from the Turaev-Viro model, which describes 3D gravity with positive cosmological constant, by an analytical continuation [104]. Here we pointed out the importance of considering the continuum limit on the boundary, in particular if one wishes to obtain a description in terms of a dual field.…”
Section: Jhep03(2016)208mentioning
confidence: 99%